APLIKASI KULIT PISANG KEPOK (Musa paradisiaca formatypica) SEBAGAI ADSORBEN ION MERKURI (Hg) - Musafira Musafira; A. Risman; Erwin Abdul Rahim (Chemistry Department, Mathematics and Natural Science Faculty, Tadulako University, 2016)
ABSTRACT The study aims are to determine the influence of the best of smooth and the best of volume eluent of the concentration of ion mercury (II) the colomn with the flow from top to bottom. These are used has a diameter 1 cm, height 35 cm and adsorbent 5 g. The variations upon the smooth which is used 10, 20 and 30 mL/minute ad the volume of eluent 10, 50, 100 and 150 mL with a concentration 60 mg/L at pH 5. This study is using random the factorial, each treatment done as much as two times. From the results showed that the best of smooth be achieved in the smooth 10 mL/minute and the best of volume eluent be achieved in the volume of 150 mL in adsorption of ion mercury (II). Keywords : Smooth, Volume of eluent, Kepok banana’s peels, Mercury.